(untitled) (Global Journal of Medical Research, 2014)
erythrocytes with 1-chloro-2, 4-dinitrobenzene (CDNB) caused quantitative conjugation of reduced glutathione (GSH) to produce S-(2, 4-dinitrophenyl) glutathione, which formed the bases for the measurement of Ery-GST activity using a spectrophotometer. Blood samples were drawn from treated non-malarious and malarious participants at time intervals of 0, 3, 6 and 18 h and measured for Ery-GST activity. The control values of Ery-GST activity of non-malarious and malarious participants were within the ranges of 3.27 ± 0.13 -12.50 ± 1.58 IU/gHb and 2.75 ± 0.16 -12.21 ± 1.20 IU/gHb respectively.